2016
DOI: 10.1016/j.electacta.2016.01.164
|View full text |Cite
|
Sign up to set email alerts
|

La0.4Bi0.4Sr0.2FeO3-δ as Cobalt-free Cathode for Intermediate-Temperature Solid Oxide Fuel Cell

Abstract: La0.4Bi0.4Sr0.2FeO3-δ (LBSF) has previously been demonstrated to show the highest electrochemical performance in a series of bismuth doped lanthanum strontium ferrite La0.8-xBixSr0.2FeO3-δ where 0  x  0.8 as the cathode for intermediate-temperature solid oxide fuel cells. The cobalt-free electrocatalyst LBSF is further investigated in the present study using thermogravimetric analysis, oxygen temperature-programmed desorption method, iodometric titration and high-temperature X-ray diffraction refinement meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…n of 1.16 for LF indicated that P1 (LF) corresponds to mass transport; while n = 0.516 for IF indicated that P2 (IF) is likely associated with the dissociation of O 2 into 2O ads . [34][35][36] The insensitivity of P3 (HF) to p O2 (n = 0.023) suggests that the HF process is likely associated with O 2À transfer across the electrode/electrolyte interface, which is a p O2 -independent process. 37 Shown in Figure 3D is the comparison of DRT plots for cells with a bare LSCF and an MP-LSCF electrode, as a function of testing time.…”
Section: It Is Shown In Figuresmentioning
confidence: 99%
“…n of 1.16 for LF indicated that P1 (LF) corresponds to mass transport; while n = 0.516 for IF indicated that P2 (IF) is likely associated with the dissociation of O 2 into 2O ads . [34][35][36] The insensitivity of P3 (HF) to p O2 (n = 0.023) suggests that the HF process is likely associated with O 2À transfer across the electrode/electrolyte interface, which is a p O2 -independent process. 37 Shown in Figure 3D is the comparison of DRT plots for cells with a bare LSCF and an MP-LSCF electrode, as a function of testing time.…”
Section: It Is Shown In Figuresmentioning
confidence: 99%
“…In the refinement, the +5 valence state of Bi doped in the B‐site was confirmed. Bi may occupy in the A site and B site. For the B‐site in the perovskite phase of ABO 3 , it has medium ion radius (0.62–1.00 Å).…”
Section: Resultsmentioning
confidence: 81%
“…Bi may occupy in the A site and B site 50,51 . For the B-site in the perovskite phase of ABO 3 , 52 it has medium ion radius (0.62-1.00 Å).…”
Section: Resultsmentioning
confidence: 99%
“…The equivalent circuit (Figure ) was generated after fitting the EIS spectra. The R 1 in this result represented the ohmic, electrolyte, and wire resistances and was not considered for the cathode ASR . At the medium‐ and low‐frequency regions, R 2 and R 3 were measured, respectively.…”
Section: Resultsmentioning
confidence: 99%